2022
DOI: 10.3389/fcell.2022.762228
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Grape Seed Proanthocyanidins on Oxidative Damage of Chicken Follicular Granulosa Cells by Inhibiting FoxO1-Mediated Autophagy

Abstract: A significant decrease in poultry egg production occurs due to ovarian aging and autophagy is one of the important factors of ovarian aging that is induced predominantly by oxidative stress. Increasing evidence showed potential roles of plant-derived grape seed proanthocyanidin (GSPs) in protecting ovarian granulosa cells (GCs) from oxidative damage, although the underlying mechanism is still unclear. Here we investigated the possible functions of autophagy involved in the preventive effect of GSPs on oxidativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Deparaffinized and rehydrated SWF sections were first processed for antigen retrieval in a 10 mM sodium citrate solution for 20 min at 100°C before BrdU detection. Immunofluorescence staining was performed using standard protocols (Zhou et al, 2022).…”
Section: Immunofluorescence Stainingmentioning
confidence: 99%
“…Deparaffinized and rehydrated SWF sections were first processed for antigen retrieval in a 10 mM sodium citrate solution for 20 min at 100°C before BrdU detection. Immunofluorescence staining was performed using standard protocols (Zhou et al, 2022).…”
Section: Immunofluorescence Stainingmentioning
confidence: 99%
“…Large numbers of studies showed that autophagy maintains the energy balance and function of cells and controls the fate of cells through different crosstalk signals, which may have an important impact on female reproductive function [ 25 ]. However, the regulation of the molecular mechanism between apoptosis and autophagy of granulosa cells has not been described fully, and the natural protective agent of granulosa cells on the target of programmed cell death (PCD) has been given a lot of attention [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to their natural antioxidant properties, PACs have been suggested as a possible protector against oxidative stress damage to various organs and tissues, including the ovaries [14][15][16] . Research has shown that PACs can effectively mitigate pathological changes in granulosa cells by inhibiting autophagy and apoptosis, which ultimately contributes towards delaying ovarian aging [17][18][19] . However, studies investigating the effects of PACs on FGSCs remains unreported.…”
Section: Introductionmentioning
confidence: 99%